Design And Fabrication Of Multi-Band Srr Sensors Using 3D Printing For Liquid Characterization - Irfan Yahaya; Ahmad Nurhelmy Adam; Shahino Mah Abdullah; Nizam Tamchek; Ahmad F. Alforidi; Ahmed Alahmadi; Mohd Ifwat Mohd Ghazali (Elsevier, 2026)
Indexed by WOS / SCOPUS / ERA